2007
DOI: 10.1186/1475-2875-6-48
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study of community factors relevant for participatory malaria control on Rusinga Island, western Kenya

Abstract: Background: Capacity strengthening of rural communities, and the various actors that support them, is needed to enable them to lead their own malaria control programmes. Here the existing capacity of a rural community in western Kenya was evaluated in preparation for a larger intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 80 publications
1
56
0
Order By: Relevance
“…Consequently, many households clean around the home (50%) and clear vegetation (32%) in an attempt to prevent malaria. Although the general consensus is that clearing vegetation is of no benefit and might even worsen malaria (Opiyo et al, 2007), evidence exists that clearing may significantly reduce malaria risk in certain environments (Hustache et al, 2007). Both of these practices may limit breeding habitat (e.g., removing artificial containers or large plants that collect water) and may prevent adult mosquitoes from resting outdoors near homes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, many households clean around the home (50%) and clear vegetation (32%) in an attempt to prevent malaria. Although the general consensus is that clearing vegetation is of no benefit and might even worsen malaria (Opiyo et al, 2007), evidence exists that clearing may significantly reduce malaria risk in certain environments (Hustache et al, 2007). Both of these practices may limit breeding habitat (e.g., removing artificial containers or large plants that collect water) and may prevent adult mosquitoes from resting outdoors near homes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have illustrated that a lack of understanding of mosquito biology is prevalent in African communities. For example, in a survey of 1,451 households in Kenya, 65% of respondents stated that they did not know what mosquito larvae look like (Opiyo et al, 2007). Educational programs have been used to increase community understanding and participation in malaria control through activities such as identifying breeding habitat, observing larval mosquitoes, and teaching techniques for suppression of mosquito breeding (Mukabana et al, 2006;van den Berg and Knols, 2006;Yasuoka et al, 2006b).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that overall knowledge, perceptions, preventive behaviors and treatment-seeking behaviors of household representatives were significantly improved after the ACPP because the villagers gained malaria control knowledge and practice by participating in the ACPP. As reported in other settings, a community-based intervention utilizing participatory tools was effective in improving community knowledge and perceptions regarding malaria control 22 , and a health education intervention was suitable for improving community knowledge in home-based management of malaria…”
Section: Discussionmentioning
confidence: 57%
“…Studies performed in Kenya, Tanzania and Cameron have also revealed poverty as an impediment to the purchase of mosquito nets (31) No association was found between ITN ownership and level of education in the study area. Earlier published reports have shown a disparity between socio-economic factors, such as educational level and ownership of nets.…”
Section: Discussionmentioning
confidence: 61%